ANALISIS KETERLAMBATAN PROYEK PEMBANGUNAN FLY OVER TAHAP 1, SIMPANG JAKABARING PALEMBANG - APRILIA, NYIMAS ARNITA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Project management is a critical factor in the implementation of a construction project. As a process, project management has the sequence / phase of the project. Starting from the stage of identification, preparation, planning, implementation and evaluation. On the flyover project Simpang Jakabaring Palembang, occurs inaccuracies time, swelling budget and plan design changes. It is certainly detrimental to the owner, the contractor and the people who are around the project. It required a review of the factors that the key to success and obstacles in the implementation of the project. To analyze the data it used descriptive method of analysis, research trying to tell solving existing problems based on the data to present, analyze and interpret. The data analyzed include project feasibility studies, implementation schedule tailored to the field survey, project planning image with the image of the project. From the analysis, it was concluded that the factors inhibiting Jakabaring flyover project is a poor time management; project specifications are less clear; lack of understanding of the officers in the field; project changes that are not manageable with good; lack of mechanisms for recording, analysis and transfer of project lessons; delay in sending the material and equipment to the site; project management in a location that is not good; lack of effective communication and coordination with project stakeholders, especially clients and consultants; the conflict in the organization owner, contractors, consultants and stakeholders. While the factors that the key to success in the implementation of the project, namely: seen from the overall project management systems such as production, information and evaluation; Project managers can observe the overall project; handling problems that occur in the project.